Contribuições para um léxico-gramática das construções locativas do espanhol - Rodrigues, Roana (2019)
Locative verbs establish a relation of localization between the elementary parts of a sentence: subject and complements (la mujer puso las llaves en la mesa). The aim of this work is to create a first version of a lexicon-grammar (GROSS, 1975) of the locative verbal constructions in Spanish. In order to do so, we first compare verbs classified as space found in the ADESSE database of verbs in Spanish (GARCÍA-MIGUEL et al., 2003), and the verbs classified as locative in the ViPEr database of verbs in Portuguese (BAPTISTA, 2013). From that intersection, 352 could potentially be part of the LGLE (Lexicon-Grammar of Locative verbs in Spanish). After thorough analysis of each lexeme, and with help of native Spanish speakers and a selection of sentences from the Web, 318 constructions were finally chosen for the LGLE. The words were classified into 10 categories, according to structural, distributional, and transformational properties, and organized into binary tables. For didactic purposes, we offer a general typology that separates the constructions into verbs with prepositions (vivió en Barcelona) and direct transitive verbs (ocupó el colegio). Beyond that, we list their main characteristics: restrictive verbs by omission (viajó -de Nicaragua- a Londres), restrictive verbs by toponymy (lo deportó a España), denominal verbs (encarceló al empresario) and phoric verbs (vino de Brasil). We also offer a brief comparative survey on locative verbal construction in Spanish and their equivalents in Portuguese, as available on ViPEr. The main divergences between the two languages are related to the false cognates and prepositions. The description of this phenomenon and its comparison the Portuguese language can contribute to the descriptive studies of natural languages, besides the application to other areas of knowledge, such as Natural Language Processing and teaching of Spanish and Portuguese as first and second languages.